1981
DOI: 10.1002/eji.1830110902
|View full text |Cite
|
Sign up to set email alerts
|

Genetic control of the expression of immunoglobulin isotypes in the responses of mice to sheep red blood cells

Abstract: Studies have been carried out on the genetic control of the expression of individual Ig classes in the responses of A/J (A) and C57BL/6J (B6) mice to sheep red blood cells (SRBC). An isotopic anti-immunoglobulin test employing Ig class-specific reagents was used to measure levels of IgM, IgA, IgG1, IgG2a, IgG2b and IgG3 anti-SRBC antibodies in sera of hyperimmunized mice. Compared with B6 mice, A mice are low IgM and IgA responders but high responders with respect to all IgG subclasses. In (B6 X A)F1 mice low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

1982
1982
1989
1989

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 29 publications
4
10
0
Order By: Relevance
“…Nevertheless, IgG1 is, together with both IgG2 subclasses, one of the most represented isotypes throughout the experiment, in contrast to the other three antibody classes, namely, IgM, IgGz, and IgA, that are poorly or not at all expressed. These results are generally in agreement with previous observations in thymus-dependent immune responses measured in short-term experiments (17)(18)(19). In the context of the present …”
Section: Antigen-specific Responses Of Normal Spleen Cells In Successivesupporting
confidence: 94%
See 3 more Smart Citations
“…Nevertheless, IgG1 is, together with both IgG2 subclasses, one of the most represented isotypes throughout the experiment, in contrast to the other three antibody classes, namely, IgM, IgGz, and IgA, that are poorly or not at all expressed. These results are generally in agreement with previous observations in thymus-dependent immune responses measured in short-term experiments (17)(18)(19). In the context of the present …”
Section: Antigen-specific Responses Of Normal Spleen Cells In Successivesupporting
confidence: 94%
“…Several different mechanisms of independent genetic control have been described to regulate both the primary IgGz, anti-SRBC response in BALB/c and C57B1/10 mice as well as hyperimmune anti-SRBC responses in C57B1/6 and A strains (19). Taken together with our studies, these results suggest that the levels of individual Ig classes produced during primary and hyperimmune responses are regulated by complex mechanisms, in clear contrast to the random recombination and deletion models.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…It has been reported that H-Y antigen is limited in distribution to the region of the acrosomal cap in mouse spermatozoa (Koo, Stackpole, Boyse, Hämmerling & Lardis, 1973). The antigen recognized by antibody MS-1 is also confined to the acrosomal region of the sperm head but was not detected on adult male spleen, epidermis or thymus tissues which are H-Y positive in transplantation and serological assays (Gasser & Silvers, 1972;Wachtel, 1977 (Silver & Winn, 1973;Haber & Winn, 1981 (Fellous, Gachelin, Buc-Caron, Dubois & Jacob, 1974). The application of homogeneous antibodies produced in vitro by hybridoma technology after appropriate immunization and screening will largely circumvent the first of these problems.…”
Section: Introductionmentioning
confidence: 99%